Cryopreservation of Aceh Swamp Buffalo (Bubalus bubalis) Semen with Combination of Glycerol and Lactose - Kartini Eriani; Nisa Sari; Rosnizar Rosnizar; Dasrul Dasrul; Suhartono Suhartono; Muhammad Rizal (Biosaintifika: Journal of Biology & Biology Education, 2017)
Aceh swamp buffaloes (Bubalus bubalis) are decreasing their population and genetic quality. This study was conducted to determine the influence of lactose and glycerol cryoprotectants on spermatozoa of Aceh swamp buffaloes after thawing. This study used completelya factorial randomized design with nine treatments, and five replications. Fresh semen of the Aceh swamp buffalo were diluted by using a combination extender lactose cryoprotectants 0 mM (L0), 60 mM (L60), 120 mM (L120) and glycerol 3% (G3), 5% (G5), 7% (G7) with the equilibration of 4 hours. The results showed that the combination of cryoprotectants L120G7 influenced significantly (P 0.05) on the quality of spermatozoa of the Aceh swamp buffalo (B. bubalis) after  thawing. The percentage of sperm motility L120G7 (42.60 ± 1.14); viability L120G7 (55.00 ± 0.71);  acrosome integrity L120G7 (52.00 ± 0.71); and plasma membrane integrity L120G7 (53.20 ± 1.48).  The combination of lactose cryoprotectants 120 mM (L120) and glycerol 7% (G7) was the best combination to maintain the quality of spermatozoa of swamp buffalo. This finding could be used to define a policy for the spermatozoa storage of Aceh swamp buffalo to artificial insemination (AI).